Hubungan Work-Life Balance dengan Work Engagement pada Guru TK X di Bandung - Salsabila Putri; Yuli Aslamawati (UNISBA Press, 2024)
Abstract. A kindergarten teacher who has job demands that have a relationship with early childhood so that it requires more patience in teaching, therefore the ability to balance personal life with work life is needed which can affect the work engagement of kindergarten teachers. This study aims to determine the relationship between work-life balance and work engagement in X kindergarten teachers. In this study, the method used was a non-experimental quantitative method involving 23 X kindergarten teachers. The measuring instrument in this study on the work-life balance variable uses Fisher's (2009) measuring instrument which has been adapted by Gunawan (2019). Meanwhile, the measuring instrument for the work engagement variable was adapted by Kristiana (2018), which refers to the UWES-9 measuring instrument of Schaufeli and Baker (2004). The data analysis used is correlational. The results of this study found that there is a relationship between work-life balance and work engagement in X kindergarten teachers of 0.657. This means that the lower the work-life balance, the lower the work engagement. Abstrak. Seorang guru TK yang memiliki tuntutan pekerjaan yang memiliki hubungan dengan anak usia dini sehingga membutuhkan kesabaran yang lebih dalam mengajar maka dari itu dibutuhkannya kemampuan menyeimbangi kehidupan pribadi dengan kehidupaan pekerjaan yang dapat mempengaruhi keterikatan kerja guru TK. Penelitian ini bertujuan untuk mengetahui hubungan work-life balance dengan work engagement pada guru TK X. Dalam penelitian ini metode yang digunakan adalah metode kuantitatif non-eksperimental yang melibatkan 23 guru TK X. Alat ukur dalam penelitian ini pada variabel work-life balance menggunakan alat ukur Fisher (2009) yang telah diadaptasi oleh Gunawan (2019). Sedangkan untuk alat ukur variabel work engagement diadaptasi oleh Kristiana (2018), yang merujuk pada alat ukur UWES-9 Schaufeli dan Baker (2004). Analisis data yang digunakan adalah korelasional. Hasil penelitian ini menemukan terdapat hubungan antara work-life balance dengan work engagement pada guru TK X sebesar 0,657. Artinya apabila semakin rendah work-life balance maka semakin rendah work engagementnya.